Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017 - Zul Hendri; Deni Agusrianti (LPPM ISNJ Bengkalis, 2019)
This research aims to determine partially the effect of company size on capital structure, the effect of profitability on capital structure, the effect of company growth on capital structure, the effect of asset structure on capital structure, and the simultaneous influence of company size, profitability, company growth and asset structure on structure capital. This research uses quantitative methods with multiple regression analysis. The tool for analyzing research data is using SMART PLS. The results of the study stated that company size (X1) had no effect on capital structure (Y), profitability (X2) had no effect on capital structure (Y), company growth (X3) had no effect on capital structure (Y), and asset structure (X4 ) affect the capital structure (Y).